Accidental resonators: theory and experiment - Bliokh, Y.P. (Вопросы атомной науки и техники, 2013)
Disorder-induced resonances in randomly-layered samples are studied theoretically and experimentally. An algorithm for the detection and characterization of the effective cavities that give rise to these resonances has been developed. This algorithm enables to find the eigenfrequencies and pinpoint the locations of the resonant cavities that appear in individual realizations of random samples. The association of any resonance with corresponding accidentally formed cavity allows determination of parameters of a given individual randomly-inhomogeneous sample by external measurements. Experimental results confirm the proposed theoretical model. Резонанси шаруватого випадкового середовища досліджуються теоретично і експериментально. Розроблено алгоритм, що дозволяє виявити області, що утворюють резонатор, відповідальний за резонансне проходження хвилі через випадково-неоднорідний зразок. Цей алгоритм дозволяє визначити резонансну частоту і характеристики випадково сформованого резонатора. Асоціація кожного резонансу з відповідним випадково сформованим резонатором дозволяє визначити параметри окремого випадково-неоднорідного зразка за допомогою зовнішніх вимірювань. Запропонована теоретична модель підтверджена експериментально. Резонансы слоистой случайной среды исследуются теоретически и экспериментально. Разработан алгоритм, позволяющий выявить области, образующие резонатор, ответственный за резонансное прохождение волны через случайно-неоднородный образец. Этот алгоритм позволяет определить резонансную частоту и характеристики случайно сформированного резонатора. Ассоциация каждого резонанса с соответствующим случайно сформированным резонатором позволяет определить параметры отдельного случайно-неоднородного образца с помощью внешних измерений. Предложенная теоретическая модель подтверждена экспериментально.